2006
DOI: 10.1086/504611
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Water Flux and Body Composition in Glaucous Gulls (Larus hyperboreus)

Abstract: Water influx rates (WIR) measured with tritiated water dilution were compared with direct measures of water and energy intake in glaucous gulls (Larus hyperboreus). Total body water (TBW) measured isotopically was also compared with TBW deter mined by body composition analysis (BCA) of the same birds. Seventeen wild gulls were captured and studied in outdoor enclosures at Ny-Å lesund, Svalbard, in July 2002. Gulls were hand-fed known quantities of Arctic cod (Boreogadus saida) or given water on the basis of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Total body water at initial capture was determined from the 18 O dilution space (Speakman 1997). Final body water content was calculated based on body mass and assuming a constant fraction of body water throughout the experiment (Shaffer et al. 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Total body water at initial capture was determined from the 18 O dilution space (Speakman 1997). Final body water content was calculated based on body mass and assuming a constant fraction of body water throughout the experiment (Shaffer et al. 2006).…”
Section: Methodsmentioning
confidence: 99%
“…A review of studies employing hydrogen isotopes in four bird species revealed a considerable variation by which the dilution space differed from actual TBW, ranging from underestimates of 2.3% to overestimates of 18% (Table 3 in Speakman et al 2001). As has been noted frequently (Gessaman 1999;Mata et al 2006;Shaffer et al 2006), there is clearly a need for more bird studies evaluating estimates of TBW and other body components measured by isotope dilution against standard proximate body composition analysis.…”
Section: Introductionmentioning
confidence: 95%
“…Speakman et al (2001; Table 3) calculated an average of 4.7% by which actual TBW was overestimated by hydrogen isotope dilution in birds, based on nine studies on four species. Additional studies using hydrogen isotopes and the plateau approach reported 8.1% for the chicken Gallus gallus (Mata et al 2006), 8.4% for glaucous-winged gull Larus glaucescens nestlings (Hughes et al 1987), and 3.3% for the glaucous gull Larus hyperboreus (Shaffer et al 2006). However, at least part of the variation among studies is due to methodological factors.…”
Section: Tbw Measured By Deuterium Dilution and The Effect Of Equilibmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate final body water volume, body mass at recapture was multiplied by the initial fractional water content, which has been validated in Shaffer et al (2006). CO 2 production was calculated using equation 2 in Nagy (1980); this equation assumes that body mass of the animal changes linearly with time.…”
Section: Field Metabolic Ratesmentioning
confidence: 99%